Electroporation-mediated genetic transformation of oil palm (Elaeis guineensis) - Chris Darmawan; Ni Made Armini Wiendi; Condro Utomo; Tony Liwang (Society for Indonesian Biodiversity, 2020)
Abstract. Darmawan C, Wiendi NMA, Utomo C, Liwang T. 2020. Electroporation-mediated genetic transformation of oil palm (Elaeis guineensis). Biodiversitas 21: 3720-3726. Novel traits introduction to existing varieties may shorten the duration of oil palm genetic improvement. This approach heavily relies on efficient plant transformation and regeneration methods. Commonly used methods such as biolistic and Agrobacterium-mediated transformation still generated low efficiency for oil palm. Therefore, it is important to find alternative transformation methods that have the potency to give better results. Electroporation is usually used for delivering genes into bacteria or plant protoplast where cell wall does not exist, however, in this research, it was used to deliver plasmid into plant tissues. The aim of this research is to establish an optimum electroporation protocol for delivering genes into oil palm calli. Electric field strength of 250, 500, 750, 1,000, and 1,250 V/cm were applied for oil palm calli electroporation. Transient GUS assay was not applicable for initial detection presumably due to oil palm endogenous GUS-like protein activity after electroporation. Delivered gene could be detected in survived calli from all tested electric field strength treatments and the highest calli growth rates were observed from 250 V/cm electroporation treatment. Overall results showed that electroporation could be used to deliver specific genes into oil palm calli and might be developed further to increase its efficiency.